Observed degree-day factors and their spatial variation on glaciers in western China - Zhang, Yong; Liu, Shiyin; Ding, Yongjian (Annals of glaciology, 2006)
The degree-day factor (DDF) is an important parameter for the degree-day model, which is a widely used method for ice- and snowmelt computation. Spatial variations of the DDF greatly affect the accuracy of snow- and ice-melt modelling. This study analyzes the spatial variability of DDFs obtained from observed glaciers in different regions of western China. The results clearly show that the DDF for a single glacier is subject to significant small-scale variations, and the factor for maritime glaciers is higher than that for subcontinental and extremely continental glaciers. In western China the factors increase gradually from northwest to southeast. In general, the regional patterns of DDFs are detectable on the glaciers due to the unique climatic environment and heat budget of the Tibetan Plateau and surrounding regions. Low DDFs can be expected for cold-dry areas, whereas high DDFs can be expected for warm-wet areas in western China. Depending on spatial variation of the characteristics of DDFs and the meteorological data, we can provide gridded degree-day models for non-monitored glaciers to reconstruct gridded historical glacier mass-balance series in western China.